In vitro and in vivo biological activity screening of Ru(III) complexes involving 6-benzylaminopurine derivatives with higher pro-apoptotic activity than NAMI-A - Trávníček, Zdeněk; Matiková-Mal'arová, Miroslava; Novotná, Radka; Vančo, Ján; Stěpánková, Kamila; Suchý, Pavel (Journal of inorganic biochemistry, 2011)
A series of novel octahedral ruthenium(III) complexes involving 6-benzylaminopurine (L) derivatives as N-donor ligands has been prepared by the reaction of [(DMSO)(2)H][trans-RuCl(4)(DMSO)(2)] with the corresponding L derivative. The complexes 1-12 have the general compositions trans-[RuCl(4)(DMSO)(n-Cl-LH)]⋅xSol (1-3), trans-[RuCl(4)(DMSO)(n-Br-LH)]·xSol (4-6), trans-[RuCl(4)(DMSO)(n-OMe-LH)]·xSol (7-9) and trans-[RuCl(4)(DMSO)(n-OH-LH)]·xSol (10-12); n=2, 3, and 4, x=0-1.5; and Sol = H(2)O, DMSO, EtOH and/or (Me)(2)CO. The complexes have been thoroughly characterized by elemental analysis, UV-visible, FTIR, Raman, and EPR spectroscopy, ES+(positive ionization electrospray) mass spectrometry, thermal analysis, cyclic voltammetry, magnetic and conductivity measurements. The X-ray molecular structure of trans-[RuCl(4)(DMSO)(3-Br-LH)]⋅(Me)(2)CO (5) revealed the distorted octahedral coordination in the vicinity of the central atom, and also confirmed that the 3-Br-L ligand is present as the N3-protonated N7-H tautomer and is coordinated to Ru(III) through the N9 atom of the purine moiety. The tested complexes have been found to be in vitro non-cytotoxic against K562, G361, HOS and MCF7 human cancer cell lines with IC(50)>100μM in contrast to the moderate results regarding the antiradical activity with IC(50)≈10(-3)M. On the contrary, in vivo antitumor activity screening showed that the prepared Ru(III) complexes possess higher pro-apoptotic activity than NAMI-A. The reduction of Ru(III) to Ru(II) and Ru(II)-species formation in tumor tissues was confirmed by means of a simple method of detection and visualization of intracellular Ru(II) by fluorescence microscopy. The originality of this method is based on the preparation of a Ru(II)-bipyridine complex in situ.
Keywords: benzylové sloučeniny; transplantace nádorů; Purines; Ruthenium; krystalografie rentgenová; protinádorové látky; Cell Line, Tumor; Drug Screening Assays, Antitumor; Mice, Inbred DBA; Kinetin; Neoplasm Transplantation; komplexní sloučeniny; Mitosis; sloučeniny ruthenia; puriny; myši inbrední DBA; nekróza; Organometallic Compounds; Benzyl Compounds; Leukemia L1210; Crystallography, X-Ray; molekulární konformace; ruthenium; Coordination Complexes; leukemie L1210; Animals; Necrosis; lidé; ženské pohlaví; Humans; zvířata; myši; apoptóza; dimethylsulfoxid; screeningové testy protinádorových léčiv; Molecular Conformation; mitóza; nádorové buněčné linie; Dimethyl Sulfoxide; Female; Mice; Ruthenium Compounds; Apoptosis; Antineoplastic Agents; organokovové sloučeniny; kinetin